2021
DOI: 10.1108/oth-12-2020-0044
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing innovative work behaviour: the role of servant leadership and creative self-efficacy

Abstract: Purpose The purpose of this paper is to explore the influence of an emerging and idealized leadership style in hospitality research such as servant leadership on employees’ innovative work behavior (IWB) via creative self-efficacy. This study also aims to investigate the moderating role of knowledge sharing between creative self-efficacy and IWB. Design/methodology/approach Data were collected from employees working in four- and five-star hotels in Pakistan. Partial least square-structural equation modeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 114 publications
(129 reference statements)
4
20
0
1
Order By: Relevance
“…Finally, this study finds that RBSE partially and positively mediated the relationship between servant leadership and taking charge. This finding mirrors previous research in which creative self-efficacy mediated the relationship between servant leadership and IWB (Jan et al. , 2021) and RBSE mediated HPWS and proactive behavior (Beltrán-Martín et al.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Finally, this study finds that RBSE partially and positively mediated the relationship between servant leadership and taking charge. This finding mirrors previous research in which creative self-efficacy mediated the relationship between servant leadership and IWB (Jan et al. , 2021) and RBSE mediated HPWS and proactive behavior (Beltrán-Martín et al.…”
Section: Discussionsupporting
confidence: 88%
“…Evidence from existing research supports the idea that RBSE could mediate the relationship between servant leadership and taking charge. For example, Jan et al (2021) found that creative self-efficacy mediated the relationship between servant leadership and IWB. Similarly, Beltr an-Mart ın et al (2017) found that RBSE mediated the relationship between high-performance work systems (HPWS) and proactive behavior.…”
Section: Rbse As a Mediatormentioning
confidence: 99%
“…The role of partial mediation is servant leadership capable of increasing innovative work behavior either through creative self-efficacy or not through creative self-efficacy. The results of this study are supported by previous research by Jan et al (2021) that creative self-efficacy can mediate the relationship between servant leadership and innovative work behavior. Servant leaders accompany and supervise the work of employees.…”
Section: Servant Leadership Creative Self-efficacy and Innovative Wor...supporting
confidence: 87%
“…Creative self-efficacy can increase employees' innovative work behavior (Akbari et al, 2021). The relationship between servant leadership and employee innovative work behavior can be developed through creative self-efficacy (Jan et al, 2021). Servant leadership contributes to employees' Innovative work behavior by enhancing their creative self-efficacy.…”
Section: The Role Of Creative Self-efficacy Mediating the Relationshi...mentioning
confidence: 99%
“…With these valuable resources in hand, employees' self-efficacy would be enhanced as they would strive to conserve these resources. Thus, based on the literature and the COR theory, it is expected that bank managers' servant leadership is likely to enhance the personal abilities and skills of bank employees, which in turn maximizes their self-efficacy beliefs (Jan et al, 2021;Ji & Hyun, 2021). It was therefore hypothesized that:…”
Section: Servant Leadership and Self-efficacymentioning
confidence: 99%